Programación de recursos para una óptima respuesta a la demanda por la penetración de energía renovable en micro-redes - Jáuregui Méndez, Gissela Rocío (2018)
With the transition from traditional electricity grids to smart grid (SG), challenges are continually presented to manage all the energy and technological resources that the SG has, always seeking to provide the customer with a quality product at the lowest cost. Based on the aforementioned, this paper formulates an objective function with its corresponding restrictions, allowing to minimize the costs of the SG through an optimal management of energy resources. The objective function includes costs of: conventional generation, generation with non-conventional renewable sources, on / off of thermal machines, storage of energy with batteries and response to demand. To solve the aforementioned mathematical problem, a solution methodology based on dynamic programming is developed, which allows visualizing the impact of the sequential implementation of energy storage and the response to demand in an electricity network. Finally, the model proposed in an REI based on the isolated electrical system of the Galapagos is evaluated, obtaining positive results from the technical and economic point of view.